COVID-19 and Microcredit: Dissecting an NGO’s Training, Financial Support, and Women Empowerment Programmes - Senyo Dotsey (Social Sciences, 2022)
This paper reports the findings from a microcredit (financial inclusion) scheme that has been operated by a non-governmental organization since 2012 in a local community in Ghana, and sustained through the COVID-19 pandemic. It first examines microfinance, women’s empowerment and third-sector organizational dynamics. It then provides an overview of microfinance in Ghana within the context of the COVID-19 pandemic, followed by dissecting the organization’s microcredit, training and women’s empowerment programmes. The following part documents the findings, with brief concluding thoughts and policy implications appearing in the last section. It is argued here that financial schemes, particularly those operated by third-sector organizations, can play a significant role in helping women in particular to deal with the secondary effects of COVID-19 by providing improved non-financial services and easy access to microfinance at low, sustainable interest rates. These findings have implications for policy formulation and sustainable development.